2022
DOI: 10.47371/mycosci.2022.08.005
|View full text |Cite
|
Sign up to set email alerts
|

<i>Morchella nipponensis </i>sp. nov. (<i>Ascomycota</i>, <i>Pezizales</i>): a paleoendemic species of section <i>Morchella</i> discovered in Japan

Abstract: The systematics of genus Morchella Dill. ex Pers. have been much clari ed with the aid of molecular biology (Masaphy, Zabari,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Species of Morchella have previously been shown to harbor eight ascospores per ascus (Clowez et al, 2014(Clowez et al, , 2015Taşkin et al, 2015;Loizides et al, 2016;Du et al, 2019), but we found that the number of ascospores produced in asci of M. galilaea varied from one to 16 (Figure 5). The number of ascospores produced in asci studied are shown in Table 1.…”
Section: Variation In Ascospore Number In Morchella Galilaeamentioning
confidence: 52%
See 1 more Smart Citation
“…Species of Morchella have previously been shown to harbor eight ascospores per ascus (Clowez et al, 2014(Clowez et al, , 2015Taşkin et al, 2015;Loizides et al, 2016;Du et al, 2019), but we found that the number of ascospores produced in asci of M. galilaea varied from one to 16 (Figure 5). The number of ascospores produced in asci studied are shown in Table 1.…”
Section: Variation In Ascospore Number In Morchella Galilaeamentioning
confidence: 52%
“…In Morchella species, mature ascospores are typically elliptical (Clowez et al, 2014(Clowez et al, , 2015Taşkin et al, 2015;Loizides et al, 2016;Du et al, 2019), however, various ascospore shapes were observed among the specimens of M. galilaea (Figure 3). Elliptical ascospores dominated and accounted for 96.1% (total 845 spores investigated from the five samples, detailed information shown in Table 1), but irregular shapes, including spherical, heart-shaped, crescent, and other forms were also observed in all investigated fruiting bodies (Table 1, Figure 3).…”
Section: Ascospore Shape and Size Are Variable In Morchella Galilaeamentioning
confidence: 99%